O debate de consciência de classe no projeto de formação em serviço social nas universidades federais da região ABEPSS Centro-Oeste - Santos, Júlio César Marinho (2024)
This dissertation aims to investigate the emphasis attributed to the formation of class consciousness in the pedagogical projects of the Social Service courses of the Federative Higher Education Institutions (IES) of the Central-West Regional of the Brazilian Association of Teaching and Research in Social Service (ABEPSS). It is assumed that highlighting the elements of determination of class consciousness is fundamental to considering the objectives of professional training in Social Service, based on a conception of education critical of bourgeois sociability. Critical professional action and the formation of class consciousness are a movement of resistance and permanent denial of the alienating and fetishistic effects of capital society, which aim to maintain and worsen the barbarism we experience. More than that, it is the notion of the need to build a new societal order, without class division, without private property, without exploration and without oppression, a radically free social system. Having as a theoretical-methodological perspective historical and dialectical materialism, documentary research was carried out with the aim of investigating the debate on class consciousness carried out in the Pedagogical Projects of the Courses. Thus, it was possible to point out the superficiality of the debate on the projects, which could compromise the materialization of the EthicalPolitical Project in professional training, especially in times of advancing commercialization of higher education and (neo)conservatism.